2020
DOI: 10.3389/fcell.2020.00483
|View full text |Cite
|
Sign up to set email alerts
|

Exosome Circuitry During (De)(Re)Myelination of the Central Nervous System

Abstract: Reciprocal neuron-glia cell communication is fundamental for the proper function of the nervous system. Oligodendrocytes are the myelinating cells of the central nervous system (CNS) that insulate and provide trophic support to neurons. This effective interaction is crucial not only for myelination but also for long-term axonal survival and neural connectivity. In recent years, exosomes have been portrayed as key players in intercellular interaction in the context of the healthy and diseased CNS. They act as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 87 publications
1
20
0
Order By: Relevance
“…Recent studies have found that exosomal contents such as myelin oligodendrocyte glycoprotein [ 155 ] , sphingomyelinase (SMase) [ 156 ] , and a variety of microRNA [ 157 160 ] are potential diagnostic biomarkers for MS. In addition, Schwann cell-derived exosomes contain a variety of neuroprotective proteins and anti-inflammatory factors [ 161 ] that play critical roles in MS via regulating myelin membrane biogenesis and providing trophic factors required for myelin maintenance [ 162 ] . For instance, exosomes which contain myelin and protective proteins against stress, were released from oligodendrocytes into the extracellular space in a calcium dependent manner [ 163 ] ; Schwann cell-derived exosomes can improve axonal regeneration after axotomy [ 164 ] , and increase nerve activity [ 165 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that exosomal contents such as myelin oligodendrocyte glycoprotein [ 155 ] , sphingomyelinase (SMase) [ 156 ] , and a variety of microRNA [ 157 160 ] are potential diagnostic biomarkers for MS. In addition, Schwann cell-derived exosomes contain a variety of neuroprotective proteins and anti-inflammatory factors [ 161 ] that play critical roles in MS via regulating myelin membrane biogenesis and providing trophic factors required for myelin maintenance [ 162 ] . For instance, exosomes which contain myelin and protective proteins against stress, were released from oligodendrocytes into the extracellular space in a calcium dependent manner [ 163 ] ; Schwann cell-derived exosomes can improve axonal regeneration after axotomy [ 164 ] , and increase nerve activity [ 165 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Brain exosomes also play an important role in central nervous system (CNS) homeostasis and can contribute to the communication between cells whether they are neighboring or distant [6]. Oligodendrocyte-derived exosomes contain myelin proteins and lipids, including Folch-Lees proteolipid, CNPase, myelin-associated glycoprotein, oligodendrocyte myelin glycoprotein, cholesterol, and sphingolipids, as well as other molecules, such as heat shock proteins, which act directly on other oligodendrocytes, neurons or microglia to regulate myelin biogenesis, degradation and maintenance, as well as to provide neuronal trophic support [88]. Additionally, oligodendroglial exosomes exert beneficial effects on neurons, potentially through the transfer of protective proteins, such as catalase and superoxide dismutase.…”
Section: Exosomes In the Nervous Systemmentioning
confidence: 99%
“…Moreover, in response to neuronal signals, OLs secrete exosomes in an electric activity-dependent manner which are internalized by neurons, affecting their activity. Conversely, neurons can also secrete exosomes that may influence myelin maintenance and regeneration [41]. In addition, OLs stimulated with glutamate secrete exosomes which, when internalized by neurons, have been shown to exert several positive effects, such as resistance to oxidative stress (via transfer of superoxide dismutase and catalase), enhancement of neuronal survival during oxygen-glucose deprivation and increased neuronal firing rate [43,77].…”
Section: Extracellular Vesicles In the Cnsmentioning
confidence: 99%
“…In addition, OLs stimulated with glutamate secrete exosomes which, when internalized by neurons, have been shown to exert several positive effects, such as resistance to oxidative stress (via transfer of superoxide dismutase and catalase), enhancement of neuronal survival during oxygen-glucose deprivation and increased neuronal firing rate [43,77]. Therefore, exosomes secreted by OLs after neuronal signals may transport components for myelin membrane biogenesis and, moreover, they may transfer trophic and survival factors to nearby axons under homeostatic and stress conditions, in order to support myelination and myelin maintenance [41].…”
Section: Extracellular Vesicles In the Cnsmentioning
confidence: 99%
See 1 more Smart Citation